Aspectos de preservação digital para fotografias forenses digitais - Silva, Ezequiel Sousa (2020)
The excerpt used in this research is aimed at a very incipient content area on this subject: forensics. The main objective is / was to combine elements brought by Information Science and Digital Forensic Science to present aspects to be considered for the preservation of forensic images, finding, based on this, the specific objectives: to present the concepts of digital preservation within the Information Science and its tools for the treatment of digital images; show the environment of Digital Forensic Science, its tools for image treatment and the relevance of images in reports; identify and map actors involved in the use of forensic images; and relate digital preservation, information retrieval and representation to the preservation of forensic images. As a result of this research, we found a great deficit in the question of digital preservation: storage and retrieval of digital images, both those that were digitized and those that came from computer analysis through forensic software, one of the vital solutions being the use of preservation metadata. The conclusion of this research summarizes the objectives achieved and emphasizes the need for more research in the area of Information Science for the field of Forensics, so that, in this time of informational avalanche, the archives can remain accessible and findable. We also consider that the requirements found during the research relate to technical data (by the Digital Forensic Science) and subjective images (by the Information Science) taking into account each type of photograph envisioned in section 6 of this thesis.